Design of Poison Lawn Springer Robot Using Proportional Integral Derivative Algorithm With Remote Control System - Scott Palmer; Jacob Wright Miller; Kieran Thomas Thorpe (Journal of Information Systems and Technology Research, 2024)
Grass is one of the plants that live on God's earth, even grass is also written in the Koran. Grass is currently also a pest for plants, so sometimes to minimize grass growth, many farmers or people eradicate grass by cutting it and even poisoning the grass. Each method used has its own risk of work accidents, such as using grass poison can experience insecticide poisoning. To anticipate this, a remote control robot was designed to sprinkle automatic grass poison using the PID (Proportional Integral Derivativ) method. The test results using measurements using a multimeter or multitester show that the robot works with a voltage of 11.1 VDC with a 5-12VDC motor with a speed of 3000 rpm and uses a motor gearbox so that it turns into a torque load of 5 Kg. Meanwhile, for control using a bluetooth module with the HC-05 interface type connected to the Android bluetooth system, the maximum distance transmission system is 0 - 10 m. For watering grass, it has 2 scales of watering from the height of the grass, grass with a height of 10 - 15 centimeters using PID 1, which is watered with a voltage of 11.1 VDC delay (t) 1.5s. Grass with a height reaching 20 - 30 using PID 2, watered with a voltage of 14.8 VDC delay (t) 3s. All lawn watering uses a 16 VDC pump motor with 1500 rpm. After the lawn watering system is implemented using the PID method, the P value = 14.56. Value I = 22.08 and value D = 15.5. The conclusion from the design of a grass poison sprinkler robot, namely the robot is able to read the type of tall grass from the ultrasonic sensor, and the robot can be controlled remotely because it uses the HC-05 interface module.